The Inclusion of sign language on the Swiss Web ecosystem (Journal of Accessibility and Design for All, 2023)
Websites are a primary means of communication between public/private organisations and the general public. Therefore, websites must be accessible to all internet users to maximise their reach and efficacy, including those with hearing disabilities using sign language.Around 10,000 deaf people and an equal number of non-deaf people – such as CODA, hard-of-hearing, interpreters, and relatives - communicate using sign language (SL) in Switzerland (SGB-FSS, 2016). SL is, in fact, the preferred means of communication among the deaf community for two primary reasons. SL provides greater detailed and accurate information than written communication for its deaf users, given its expressive nature and many deaf people consider it part of their identity. In modern society, the Web has revealed itself as a new medium to convey and receive information since its inception more than 30 years ago. However, little is known about the actual presence of SL in the Web, particularly in the Swiss web ecosystem.This study showcases the preliminary results of our research into the presence of sign language in the Swiss web ecosystem. Looking at 97 websites of Swiss public institutions, universities, companies, news portals, and online shops, we investigated whether videos on their websites provided SL interpretation. We found that less than a third of the websites investigated had one or more videos. We then analysed the common characteristics of a subset of the videos (French-speaking Swiss SL videos) and checked whether they provided an equivalent of the websites’ textual content. We found that those videos were mostly integrated on a web page dedicated to accessibility. They also had non-oral subtitles and were typically medical or legal-themed. Based on our results, we could argue that the presence of SL in the Swiss web ecosystem is anecdotal, especially if compared with the amount of written information that is included on those websites.